La science en débat en Amérique latine - Adrian Feld; Pablo Kreimer (Revue d'anthropologie des connaissances)
By the end of the 60’s and the early 70’s a large critical wave on the role of science and technology appears throughout the world. Similarly, in Argentina, this movement was expressed by the creation -from 1968 and 1969-of institutional spaces for public debate and knowledge production on science and technology. The confrontation of ideas revealed a process of politicization of science that had quite different meanings: on the one hand, a “moderate” group was looking for analytical and normative tools for the implementation of public policies of S&T and, on the other hand, the “radicals” which impelled the integration of science and technology in politics itself. This paper proposes to focus on the radical approach, whose most prominent representative was Oscar Varsavsky. This allows us to analyze: a) the process of “politicization / radicalization” of science emerging in the late sixties; b) the main points of confrontation between Varsavsky’s political and epistemological positions against other important actors of the time; c) the emergence of new channels to diffuse the debates on science and technology, as the journal Ciencia Nueva, and the arguments around “science-ideology” relationships; d) the adoption and reinterpretation of Varsavsky’s discourse by the political and trade union organizations of the time.